Pobreza, etnia y exlusión, la cultura de la diferencia. - Béjar, Héctor (2005)
Providing an overview of traditional and new elements of the debate on poverty, ethnicity and social exclusion, this article links the issue of social exclusion with the origin of nation-states, social relations, multicultural societies and interculturalism. It also presents some proposals for social inclusion and intercultural relations based on a philosophical discussion.